Unilateral positive-negative myoclonus in Creutzfeldt-Jakob disease - Ohnari, Keiko; Matsunaga, Kaoru; Uozumi, Takenori; Tamagawa, Akira; Hashimoto, Tomoko; Tsuji, Sadatoshi (Movement disorders, 2006)
We report a patient with Creutzfeldt–Jakob disease who presented asymmetric myoclonus. Positive–negative myoclonus was seen only in the right extremities in association with periodic synchronous discharges (PSDs) on the electroencephalogram, although pure positive myoclonus was rarely seen in the left extremities, independently in PSDs. The duration of the silent period recorded in the right‐hand muscle produced by transcranial magnetic stimulation was much longer than that in the left‐hand muscle or that in normal subjects. Brain MRI diffusion‐weighted images showed signal hyperintensities in the putamen and cerebral cortex, including the motor cortex, predominantly on the left side. © 2006 Movement Disorder Society